Internet Empowerment, Political Socialization, and the Echo Chamber Phenomenon of Taiwan’s Youth Generation - Ling Feng Li; Li Liang You (SAGE Open)
With the widespread use of the Internet and the rise of new media, these platforms have empowered the young generation in Taiwan to independently learn, express, and communicate. They have also contributed to the prominence of the echo chamber phenomenon, and the resulting social division and mutual exclusion have gradually attracted attention from the academic community. Nevertheless, the conceptual connotation of the term echo chamber in political participation urgently needs clarification. In light of this, the study focuses on the echo chamber phenomenon of political participation among Taiwan’s youth within the context of network empowerment. Constructing the research framework based on defining and demarcating the echo chamber phenomenon, this article utilizes the theory of political socialization. The in-depth interview method is then employed to analyze and confirm the existence of the echo chamber phenomenon in Taiwan. The study reveals that the echo chamber, a term originating in digital culture, do manifest in real political engagement. Their formation is closely associated with patterns of political socialization shaped by empowerment and extensive Internet use. Both political parties and social groups engage in behaviors associated with the echo chamber, and different parties have distinct ways of utilizing the echo chamber.